Dünya atşunaslugunun kemala gelmeginde ahalteke atlarunun ornu. Halkara ulmu konferensiyasuna niyetlenen maglumatlar = Rol ahaltekinskogo konya v formirovanii mirovogo konnozavodstva. Materialı mejdunarodnoy nauçnoy konferentsii = The role of ahalteke horse in the formation of world horse-breeding. Materials for the international scientific conference (Aşgabat)
253 s.